A CRITICAL ANALYSIS OF CHIEF EXECUTIVE OFFICER SUCCESSION LITERATURE AND FUTURE RESEARCH AGENDA - Hasanah, Nur (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
Abstract This paper has two objectives. Firstly, it aims to examine prior research on CEO succession in order to establish a comprehensive framework, building upon the contributions of Berns & Klarner (2017) to the present. Secondly, it proposes a future research agenda concerning the board’s role in CEO succession procedures. Articles in ten leading journals listed in EBSCO, ScienceDirect, and Scopus databases were selected. Conceptual and relational analyses were taken to achieve the objectives of this paper. At last, this paper produces a comprehensive framework of CEO succession research built on and extended from the prior research. A future research agenda concerning CEO succession is also proposed.